Invasive mosquitoes, larval competition, and potential implications for vector competence - Bevins, Sarah, author; Moore, Janice, advisor (Colorado State University. Libraries, 2007)
Aedes albopictus is an invasive mosquito species which established rapidly in the US. It is characterized as an aggressive biter, prolific breeder, and dominant larval resource competitor. Declines in resident mosquito species have followed its arrival, and species that persist often emerge from shared larval habitats as small, nutritionally deprived adults. Aedes albopictus is a competent disease vector in both its native range and in areas of recent establishment. It therefore has the potential to alter vector-borne disease transmission either directly, by creating a new pathogen association, or indirectly, via interactions with native mosquito vectors.

Ochlerotatus triseriatus is a native mosquito species that shares larval habitat with Ae. albopictus in regions of sympatry. Interspecific competition has been documented between these two species. Replacement series experiments were carried out in the laboratory to determine the extent of intraspecific and interspecific larval competition between Oc. triseriatus and Ae. albopictus. Competitive consequences were only documented when nutrition was added to treatments in a single pulse, versus the same nutritional amount being gradually added over time. Resource amount and input appear to determine if the two species co-exist or if the native species is competitively excluded in the laboratory.

The invasive species was a dominant larval resource competitor, decreasing native species survival to adulthood. Decreased Oc. triseriatus survival, however, led to reduced intraspecific competition, with survivors from high mortality treatments being larger than survivors from low mortality treatments. These larger native females were more likely to host-feed, and more likely to develop both La Crosse virus midgut and disseminated infections. Results indicate that presence of the invasive species reduced native species survival, but the resulting reduction in intraspecific competition leads to fewer surviving females that have an enhanced ability to participate in La Crosse virus transmission. Ochlerotatus triseriatus fecundity was also reduced when Ae. albopictus was present, but vertical transmission rates of LACV were unaffected.

Field surveys revealed rapid spread and establishment of a newly introduced mosquito species, Ochlerotatus japonicus. Its pervasive presence highlights the need for increased understanding and monitoring of invasive vector species, as well as vigilance in preventing the arrival of others.
Keywords: Aedes albopictus; La Crosse virus; larval competition; mosquitoes; Ochlerotatus japonicus; Ochlerotatus triseriatus; vector competence; ecology; entomology